A Thr/Ser dual residue motif in the cytoplasmic tail of human CD1d is important for the down‐regulation of antigen presentation following a herpes simplex virus 1 infection. Issue 2 (12th September 2013) - Liu, Jianyun; Glosson, Nicole L.; Du, Wenjun; Gervay‐Hague, Jacquelyn; Brutkiewicz, Randy R.
Summary CD1d‐restricted T (natural killer T; NKT) cells are important for controlling herpesvirus infections. Interestingly, herpes simplex virus (HSV) can down‐regulate CD1d‐mediated activation of NKT cells. We have previously shown that the Thr322 residue in the cytoplasmic tail of human CD1d is important for its intracellular trafficking and functional expression. We proposed that the phosphorylation of T322 is a signal for CD1d lysosomal targeting and subsequent degradation. In the current study, we generated dual mutants by substituting the T322 and S323 residues of wild‐type (WT) CD1d with Ala (non‐phosphorylatable) or Asp (mimicking phosphorylation) and ectopically expressed them in human embryonic kidney 293 cells. We found that the surface expression levels of the CD1d mutants was in this order: T322AS323A > WT > T322A > S323A > S323D > T322D > T322DS323D. Our results therefore suggest that mimicking the phosphorylation of both T322 and S323 has a cumulative negative effect on the functional expression of CD1d. As previously reported, we also found that upon an HSV infection, antigen presentation by WT CD1d is reduced and the CD1d molecule is degraded. Interestingly, the T322A/S323A double mutation inhibited CD1d degradation and rescued CD1d‐mediated antigen presentation following an HSV‐1 infection. This suggests that the T322/S323 dyad may be phosphorylated, which then targets CD1d for lysosomal degradation post‐infection as a means of immune evasion, explaining (at least in part) the reduced antigen presentation observed. Hence, our findings strongly suggest that T322 and S323 form a dual residue motif that can regulate the functional expression of CD1d during a viral infection.